Towards elimination of viral hepatitis in the Czech Republic, Hungary, Poland and Slovakia: insights from the Viral Hepatitis Prevention Board (VHPB) - Flisiak, Robert; Frankova, Sona; Jindal, Sakshi; Aster, Viktor; Hunyady, Bela; Makara, Mihaly; Kristian, Pavol; Stanekova, Danica; Zarębska-Michaluk, Dorota; Valckx, Sara; Hendrickx, Greet; Damme, Pierre; et al. (Clinical and Experimental Hepatology, 2026)
The Visegrad Group – the Czech Republic, Hungary, Poland and Slovakia – face shared challenges in preventing and controlling viral hepatitis. A regional meeting convened by the Viral Hepatitis Prevention Board evaluated health systems, epidemiology, and national policies, revealing accomplishments and needs for prevention, screening, diagnosis, and linkage to care of viral hepatitis. Universal hepatitis B (HBV) vaccination exists, yet vaccine hesitancy and incomplete coverage threaten progress, while surveillance and registries remain fragmented. Access to hepatitis C (HCV) treatment has improved recently, but remains centralized, with limited engagement of marginalized populations. Elimination of HCV by 2030 is unlikely due to insufficient screening, COVID-19-related healthcare disruptions, and weak political commitment, whereas HBV control depends on maintaining high vaccination coverage and robust monitoring. Participants called for harmonized national guidelines, strengthened regional collaboration, and sustainable action plans backed up by political commitment. Urgent, coordinated efforts are needed to achieve the WHO 2030 elimination goals.